2017
DOI: 10.1016/j.sjbs.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Variation and significance of serum leptin, blood lipid level, adiponectin, NO and TNF-α for patients with non-traumatic ischemic necrosis of the femoral head

Abstract: The levels of serum cholesterol, triglyceride level, low density lipoprotein level, apolipoprotein B level, leptin, NO and TNF-α levels in serum of INHF patients were positively correlated with the condition of INHF patients, and high density lipoprotein levels, Apolipoprotein A1 levels and adiponectin levels were negatively correlated with INHF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…One month after embolization, the myometrium had almost no lysis and necrosis of myometrial smooth muscle cells, suggesting that the MSAH did not affect the blood flow of peripheral blood vessels and did not cause tissue ischemia and necrosis. It has been reported (Prieto-Moure et al, 2017;Xu et al, 2017) that tissue cells produce and release TNF-α after tissue ischemia to activate T cells, promote the production and secretion of IL-1β, and induce inflammation. In this study, we found that the levels of TNF-α and IL-1β both in the plasma and uterine tissue were significantly lower in the MSAH group than in the Gelfoam group and the Coil group, suggesting that MSAH can induce a slight inflammatory reaction and does not cause the peripheral tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…One month after embolization, the myometrium had almost no lysis and necrosis of myometrial smooth muscle cells, suggesting that the MSAH did not affect the blood flow of peripheral blood vessels and did not cause tissue ischemia and necrosis. It has been reported (Prieto-Moure et al, 2017;Xu et al, 2017) that tissue cells produce and release TNF-α after tissue ischemia to activate T cells, promote the production and secretion of IL-1β, and induce inflammation. In this study, we found that the levels of TNF-α and IL-1β both in the plasma and uterine tissue were significantly lower in the MSAH group than in the Gelfoam group and the Coil group, suggesting that MSAH can induce a slight inflammatory reaction and does not cause the peripheral tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlation between obesity and ONFH, it is important to include additional factors such as hyperlipidemia. However, further investigation is required to confirm this relationship [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADPN and LEP, which are mainly secreted by adipose tissue, may provide a bridge between energy and bone metabolism by mediating the balance of bone mass and fat content . We observed similar increases in ADPN levels and decreases in LEP levels following GC therapy in both groups (Fig.…”
Section: Discussionmentioning
confidence: 99%